1999
DOI: 10.1074/jbc.274.4.2286
|View full text |Cite
|
Sign up to set email alerts
|

Critical Nucleotides in the Upstream Region of the XylS-dependent TOL meta-Cleavage Pathway Operon Promoter as Deduced from Analysis of Mutants

Abstract: The Pm promoter, dependent on TOL plasmid XylS regulator, which is activated by benzoate effectors, drives transcription of the meta-cleavage pathway for the metabolism of alkylbenzoates. This promoter is unique in that in vivo transcription is mediated by RNApolymerase with different sigma factors. In vivo footprinting analysis shows that XylS interacted with nucleotides in the ؊40 to ؊70 region. In vivo and in vitro methylation of Pm shows extensive methylation of T at position ؊42 in the bottom strand, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
68
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 28 publications
6
68
0
Order By: Relevance
“…1). Single point mutations in the binding site revealed that nucleotides located at Ϫ48 to Ϫ45 and at Ϫ58, Ϫ59, Ϫ61, and Ϫ69 are the most critical bases for appropriate XylS-Pm interactions (7)(8)(9). In vitro footprints obtained with a tagged XylS protein immunoadsorbed onto glass beads supported this organization (10).…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…1). Single point mutations in the binding site revealed that nucleotides located at Ϫ48 to Ϫ45 and at Ϫ58, Ϫ59, Ϫ61, and Ϫ69 are the most critical bases for appropriate XylS-Pm interactions (7)(8)(9). In vitro footprints obtained with a tagged XylS protein immunoadsorbed onto glass beads supported this organization (10).…”
mentioning
confidence: 80%
“…In vivo and in vitro methylation assays of Pm show extensive methylation of T at position Ϫ41 in the bottom strand, suggesting the presence of a key distortion point that may favor XylS/ RNA polymerase interactions (8). In this connection, it has been shown that XylS contacts residues 291 and 289 of the ␣-subunit of RNA polymerase (13).…”
mentioning
confidence: 99%
“…The Ϫ35 box of P BC clearly deviates from the consensus sequence of 70 -dependent promoters of E. coli, and two direct repeats have been found upstream of this box (253). The presence of direct repeats in this position appears to be a common feature of the binding sites for AraC-like regulators such as the XylS protein, which recognizes direct repeats leading to the formation of a dimer that interacts with the RNA polymerase and hence activates transcription from the cognate promoter (118).…”
Section: Transcriptional Activatorsmentioning
confidence: 99%
“…The protein bound along one side of the DNA, covering four helices and thereby making specific contacts in four adjacent major grooves (102). By earlier sitedirected mutagenesis studies, a consensus direct repeat (TGCA-N 6 -GGNTA), which is present twice in the P m promoter between Ϫ35 and Ϫ49 and between Ϫ56 and Ϫ70, had been identified as the binding determinant (70,78,107). In the presence of m-toluate, the degree of protection by XylS on the P m promoter increased (102,103), suggesting that the affinity of XylS to its binding site had changed.…”
Section: Mechanisms Of Activationmentioning
confidence: 99%
“…In the presence of m-toluate, the degree of protection by XylS on the P m promoter increased (102,103), suggesting that the affinity of XylS to its binding site had changed. Subsequent in vivo methylation studies showed an altered methylation protection pattern of the XylS-bound region in the presence of m-toluate, which indicates that conformational changes take place under inducing conditions (78).…”
Section: Mechanisms Of Activationmentioning
confidence: 99%